Arago (1810): the first experimental result against the ether - Ferraro, Rafael (2005)
Ninety five years before special relativity was born, Arago attempted to detect the absolute motion of the Earth by measuring the deflection of starlight passing through a prism fixed to the Earth. The null result of this experiment gave rise to Fresnel's hypothesis of an ether partly dragged by a moving substance. In the context of Einstein's relativity, the sole frame which is privileged in Arago's experiment is the proper frame of the prism, and the null result only says that Snell's law is valid in that frame. We revisit the history of this premature first evidence against the ether theory and calculate Fresnel's dragging coefficient by applying Huygens' construction in the frame of the prism. We expose the dissimilar treatment received by the ray and the wavefront as an unavoidable consequence of the classical notions of space and time.